2022
DOI: 10.1111/jan.15486
|View full text |Cite
|
Sign up to set email alerts
|

Nurse–patient interaction during the Covid‐19 pandemic: Creating and maintaining an interactive space for care

Abstract: Aims: To explore nurse-patient interactions during the Covid-19 pandemic from both nurses' and patients' perspectives.Design: Qualitative study using constructive grounded theory.Methods: A total of 34 patients and 49 nurses from acute and home care settings participated in individual or focus group interviews between December 2020 and May 2021. Data were analysed by a team of researchers using coding, memo-writing, theoretical sampling and constant comparison and integration. Results:We identified the creatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…4 During the height of the coronavirus crisis, the unparalleled value of innovation in healthcare was proven through the introduction of new and innovative healthcare models to better respond to the unique needs of coronavirus patients while protecting the health of the care providers. [5][6][7] Technological innovations included the use of artificial intelligence to facilitate the screening and diagnosis of suspected patients, digital apps for surveillance and contact tracing, and telenursing and telemedicine to deliver medical and nursing care to remote clients. 5,6 The utilization of an innovative interactive space for care to deliver patientcentered nursing care was likewise found to significantly improve health outcomes in patients during the height of the pandemic.…”
Section: Leadership Styles and Nurses' Innovative Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 During the height of the coronavirus crisis, the unparalleled value of innovation in healthcare was proven through the introduction of new and innovative healthcare models to better respond to the unique needs of coronavirus patients while protecting the health of the care providers. [5][6][7] Technological innovations included the use of artificial intelligence to facilitate the screening and diagnosis of suspected patients, digital apps for surveillance and contact tracing, and telenursing and telemedicine to deliver medical and nursing care to remote clients. 5,6 The utilization of an innovative interactive space for care to deliver patientcentered nursing care was likewise found to significantly improve health outcomes in patients during the height of the pandemic.…”
Section: Leadership Styles and Nurses' Innovative Behaviorsmentioning
confidence: 99%
“…5,6 The utilization of an innovative interactive space for care to deliver patientcentered nursing care was likewise found to significantly improve health outcomes in patients during the height of the pandemic. 7 Therefore, it is vital for healthcare organizations to find ways to improve innovative behaviors among nurses and implement strategies to support these behaviors.…”
Section: Leadership Styles and Nurses' Innovative Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to a reduced capacity to perform non-essential intimate bodily tasks, especially if they are not directly related to the patient's immediate medical needs. 16,17 Furthermore, the psychological and emotional burden of the pandemic may have adversely affected the work performance of nurses and their capacity to accomplish all essential nursing care tasks in a timely manner. 24,25 Collectively, these circumstances have led the remaining nurses to prioritize nursing care activities that are deemed vital to optimizing physiological functioning in patients with COVID-19, such as medication administration and respiratory and breathing treatments, over basic nursing care tasks.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Due to pandemic-related factors (eg, higher transmissibility of the virus, surge in patients, increased workloads), interactive spaces where caregiving and receiving takes place became limited, resulting in nurses being unable to fully meet patient needs. 16,17 Numerous studies have shown that the COVID-19 pandemic forced nurses to prioritize patient care activities that are vital for maintaining physiological functioning, such as respiratory treatment, drug administration, and positioning to maintain respiratory functions, 18,19 over other patient care elements addressing psychological and affective needs. 20 This situation was further amplified by the ongoing nurse staffing shortage, increasing rates of nurses quitting their jobs, 21,22 unfavorable working conditions, and a lack of organizational support.…”
mentioning
confidence: 99%